Architektūros ir dailės prasmių paieška išplėstiniame šiuolaikinės meninės kūrybos lauke - Novickas, Audrius (Journal of Architecture and Urbanism, 2011)
Search for new meanings in the expanded field of contemporary architecture and art The paper deals with contemporary practice that crosses the boundaries of art and architecture, connects aesthetic and social issues, theoretical discourse and interdisciplinary practice. It also stresses the importance of integration of a new language of arts into the architectural study process. Investigation is aimed not just towards changes of definitions of separate fields of art and architecture but also towards analysis of peculiarities of developments in the expanded field of contemporary practice. Seeing the developments in arts through the focus on expanded field implies acceptance of non-hierarchical and open mode of their interrelations and shift of the aim of interaction from search of new order to search of new meanings. The differences of arts are approached as sources of tension necessary to create new meanings and the idea of conflicting coexistence is used in collaborative and crossover art projects to negotiate the borderlines of practice zones, and to transform them into intermediate zones of hybrid identities. The principle of conflicting coexistence and interaction of arts is also explored to rethink the nature of underlying oppositions between social and abstract, imaginative and real, ideal and surviving. The experience of interdisciplinary art practice by the architecture students is shared via example of installation course at VGTU, Faculty of Architecture. It is revealed that the course is aimed at the critical spatial practice. It starts with discourse that leads to means and methods not necessarily traditionally associated with art. These means and methods are used to create complex site-specific interventions to scale 1:1. The installations not only allow the rethinking of spatial, temporal and social aspects of place but also changing actual experience of space. The results of the installation course are summed-up by the insight that artistic language of students’ works is not self referential but also intended to plenty the functions of space, to free its perception from practical and symbolic conventions, to connect local cultural, politic contexts with wider or global issues, to multiply meanings of art. Article in Lithuanian. Santrauka. Nagrinėjami šiuolaikiniai menų reiškiniai, peržengiantys dailės ir architektūros sričių ribas, sujungiantys estetinius ir socialinius kūrybos aspektus, teorinį diskursą ir tarpdisciplinines praktikas; taip pat aptariama menų sąveikos naujausių tendencijų puoselėjimo architektūros studijose svarba ir patirtis. Siekiama interpretuoti ne tiek naujausius atskirų meno sričių tapatumo poslinkius, kiek išplėstiniame kūrybos lauke, apimančiame ir architektūrą, ir dailę, vykstančius dinaminius procesus. Išryškinama, kad išplėstiniame lauke skleidžiasi nehierarchiškas ir atviras menų tarpusavio santykis, o sąveika kreipiama ne tiek tvarkos, kiek koncepcijų, arba kitaip tariant, naujų prasmių kūrimo link. Architektūros ir dailės sričių skirtumai tokių meno reiškinių atveju akcentuojami permąstant ir perkuriant pamatines kūrybines įtampas tarp dominavimo ir bendradarbiavimo, socialumo ir abstraktumo, tarp vaizduotės ir tikrovės, tarp idealumo ir orientacijos į išgyvenimą. Šiuolaikinių menų sąveikos tendencijų puoselėjimo studijų procese patirtis pristatoma nagrinėjant instaliacijų kurso VGTU Architektūros fakulteto studijų programoje rezultatus. Išryškinama, kad šio kurso tikslas yra kritiniu mąstymu ir intervencinėmis strategijomis pagrįstos erdvinės kūrybos idėjų ir praktinės patirties įsisavinimas. Atskleidžiama, kad instaliacijos skatina kontekstualizuoti ir konceptualizuoti meninės kūrybos procesą ir jo rezultatą, teikia galimybes realiai keisti erdvę ir dauginti jos paskirtis. Reikšminiai žodžiai: architektūra, dailė, instaliacija, ribos, išplėstinis laukas, simbiozė, erdvinis, kritinis, socialinis, intervencija, utopija, mikrotopija, realizuojamumas. First Publish Online: 22 May 2013